Komunikasi Word of Mouth: (Studi Kasus Strategi Penjualan of Mouth Offline dan Online pada Generasi Milenial di Ibat Daun Palembang) - Leo Ferdian Fauzi (Institut Nalanda, 2024)
This study aims to determine the marketing strategy of Rumah Makan Ibat Daun Palembang, as well as the obstacles in carrying out promotions using word of mouth on-line and off-line. The paradigm of this research in constructivism is the result of socio-cultural construction in communication activities using word of mouth. This type of qualitative research with a case study approach. Data collection techniques using interviews and non-participant observation, the researcher acts as an observer. The research findings prove that the Ibat Daun Restaurant uses online word of mouth communication in marketing its restaurant products through instagram, facebook, blogger, websites and the Sriwijaya Post newspaper. The communication used uses five dimensions, namely word of mouth, namely Talkers: consumers, management, family , and best friend; Topics: about RM. Ibat Leaf; Tools: verbal communication; Talking Part: individuals and communities; and Tracking: giving questionnaires to and interviewing consumers. Based on the findings, it proves that the reason Ibat Daun Restaurant uses word of mouth communication is because word of mouth communication does not require a large amount of money, while the obstacles experienced are hoaxes circulating on-line or off-line which can give the restaurant a bad reputation. Ibat Leaf. The solution adopted is to provide an attractive lay-out on social media and provide the best service, using the services of influencers